The effect of caffeine ingestion on 8 km run performance in a field setting - Bridge, C. A.; Jones, M. A. (Journal of Sports Sciences, 2006)
The aim of this study was to assess the effect of caffeine ingestion on 8 km run performance using an ecologically valid test protocol. A randomized double-blind crossover study was conducted involving eight male distance runners. The participants ran an 8 km race 1 h after ingesting a placebo capsule, a caffeine capsule (3 mg · kg-1 body mass) or no supplement. Heart rate was recorded at 5 s intervals throughout the race. Blood lactate concentration and ratings of perceived exertion were recorded after exercise. A repeated-measures analysis of variance (ANOVA) identified a significant treatment effect for 8 km performance time (P < 0.05); caffeine resulted in a mean improvement of 23.8 s (95% confidence interval [CI] = 13.1 to 34.5 s) in 8 km performance time (1.2% improvement, 95% CI = 0.7 to 1.8%). In addition, a two-way (time × condition) repeated-measures ANOVA identified a significantly higher blood lactate concentration 3 min after exercise during the caffeine trial (P < 0.05). We conclude that ingestion of 3 mg · kg-1 body mass of caffeine can improve absolute 8 km run performance in an ecologically valid race setting.